The Influence of Industrial Internship and Self-Efficacy on Teaching Readiness of Mechanical Engineering Education Graduates - Muhammad Akhyar; Wita Hidayati; Suharno Suharno; Ranto Ranto (STAI Hubbulwathan Duri, 2024)
The purpose of this research is to find out the influence of industrial apprenticeship and self-efficacy on teaching readiness. The research method used is the survey method. The population in this study were 118 graduates of mechanical engineering education who taught as teachers. The sampling technique used random sampling with as many as 91 respondents. The results of the data have been normally distributed and linear. The results of the data did not occur multicollinearity with a tolerance value of 0.399 0.10 and VIF 2.508 10. The results of the data did not show heteroscedasticity. The regression equation obtained is Y = 4,443 + 0,464X 1 + 0,578X 2. Based on the results of the industrial apprenticeship T-test on teaching readiness of 4.510 1.987 where Tcount Ttable, there is a partial effect of industrial apprenticeship on teaching readiness. The results of the T-test, self-efficacy on teaching readiness amounted to 4.840 1.987 where Tcount Ttable, so there is a partial effect of self-efficacy on teaching readiness. The results of the F hypothesis test (Fcount Ftable is 97.347 3.10. Based on the coefficient of determination, industrial apprenticeship and self-efficacy affect teaching readiness by 0.689. So, in conclusion, there is a positive influence between industrial apprenticeship and self-efficacy on readiness for teaching graduates of Mechanical Engineering Education.